Green Innovation in Daily Operations: An Ethnographic Exploration of Sustainability-Driven Systemic Change in Retail Organizations - Isma Elan Maulani (Politeknik Siber Cerdika Internasional, 2025)
In response to mounting global environmental challenges and growing consumer demand for sustainable business practices, retail organizations are increasingly adopting green innovations in their daily operations. This research examines the implementation and experience of sustainability-driven systemic change within retail settings through an ethnographic lens. The primary objective is to explore the cultural, operational, and organizational transformations that support green innovation in everyday retail practices. Employing a qualitative ethnographic methodology, data were collected through participant observation, semi-structured interviews, and document analysis in three large retail organizations known for their sustainability initiatives. The study involved 36 participants, including managers, staff, and customers, selected through purposive sampling. Data were analyzed using thematic coding and triangulated to ensure reliability and validity. Findings reveal that leadership commitment, employee engagement, sustainable supply chains, customer co-creation, and adaptive learning cultures influence successful integration of green innovation. These elements work together to foster a systemic shift in organizational behavior and identity toward sustainability. The results highlight that green innovation in retail is not merely a set of isolated practices but a dynamic, value-driven transformation embedded in the organizational culture. This study contributes to the literature by offering a grounded, ethnographic understanding of how green practices become institutionalized in retail contexts. The findings offer practical insights for retail leaders seeking to integrate sustainability into their core operations and strategies, with implications for policymaking, employee training, and customer relationship management.